テイチャクヒョウジョウ ノ ビキショウ・ネツシュウシ - 中川, 清隆; ナカガワ, キヨタカ; Nakagawa , Kiyotaka (1997)
P(論文) 南極リュツォ・ホルム湾オングル海峡中央部において, 1990年の3月末-12月初めの間, 積雪層を伴った定着氷上の微気象が観測された。日射量の年変化に対応して, 放射収支が年変化した。放射収支は極夜が明けるまでは負であったが, 10月以降正に転じた。放射収支の変化に対応して, 大気から積雪層への顕熱輸送量も定着氷から積雪層への熱伝導量も変化した。特に, 顕熱輸送量は放射収支の変化のミラーイメージの様な変化を示した。卓越風の風速が増すにつれて, 気温と湿度が増加し, 放射による熱損失や大気から積雪への顕熱輸送量, 定着氷から積雪層への熱伝導量は減少した。 Micrometeorological conditions were observed over fast ice with overlying thick snow cover and underlying deep sea approximately in the center of Ongul Strait in Lutzow-Holm Bay, Antarctica, from the end of March to the beginning of December in 1990. In response to the annual change of solar radiation, the radiation balance had an annual variation; the radiation balance was negative for a period including the polar night, and changed to positive after October. Corresponding to the radiation balance, both sensible heat flux from the air to the snow and the conductive heat flux from the fast ice to the snow changed. Especially, the sensible heat flux changed with the radiation balance like a mirror image. As the prevailing wind velocity increased, the temperature and humidity increased, and the radiative heat loss, the sensible heat flux from the air to the snow, and the conductive heat flow from the fast ice to the snow decreased. departmental bulletin paper